In vitro effect of cocoa leachates on growth and development of Moniliophthora roreri ([Cif.] H.C. Evans et al.) isolated from Theobroma cacao (L.) - Gómez-Gutierrez, Sandra Victoria; Beltrán-Acosta, Camilo Rubén; Gómez-Caro, Sandra (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The cocoa crop is part of the peasant’s economic activity and agroforestry systems in many regions of Colombia and the world. Its yields are diminished by phytosanitary problems, being the frosty pod rot caused by the fungus Moniliophthora roreri, the most limiting disease with decreases in production of over 90%. In this study, samples of cocoa leachates from commercial producing farms were characterized and the antifungal activity of sterilized, non-sterilized, and filtered cocoa leachates against M. roreri was evaluated under in vitro conditions, at concentrations of 1, 2, 5, 10, and 15%. Monosporic isolates of the pathogen were obtained from diseased fruits collected from cocoa-producing farms in the municipality of Yacopi in Cundinamarca, Colombia. The effect of leachates on M. roreri conidial germination, mycelial growth, and inoculum production was evaluated. It was found that non-sterilized cocoa leachates at all concentrations caused 100% reduction on the three variables evaluated, while sterilized leachates generated the same effect at concentrations of 10 and 15%. Filtered leachates showed no inhibitory effect on the radial growth of the pathogen, but they caused a reduction of conidial germination of 89.9, 90.5 and 95.9% at concentrations of 5, 10, and 15%. The presence of malic, citric, and ascorbic acids, compounds such as NH4, PO4, and NO3, and elements such as Ca, K, Na, Mg, and Cl in the evaluated leachates was identified using high-efficiency liquid chromatography and physicochemical analysis. This research showed the potential of cocoa leachates, even at low concentrations, for the control of M. roreri, which can be attributed to the action of specific compounds such as those found in chromatographic tests.